Skateboarding`s Olympic journey: do the performance profiles of top athletes remain consistent? - Fouillot, C.; Saulière, G.; Antero, J.; Sedeaud, A.; Toussaint, J.-F. (Frontiers in Physiology, 2025)
Introduction: Since its inclusion in the Tokyo 2020 Olympics, skateboarding has highlighted diverse age profiles among elite athletes. This study aims to characterize the relationship between age and performance in Street Skateboarding and examine how it has evolved with the sport`s growing professionalization.